Moderating Effect of Pre-Exposure Prophylaxis Use on the Association Between Sexual Risk Behavior and Perceived Risk of HIV Among Brazilian Gay, Bisexual, and Other Men Who Have Sex With Men: Cross-Sectional Study - Kevin James Blair; Thiago S Torres; Brenda Hoagland; Daniel R B Bezerra; Valdilea G Veloso; Beatriz Grinsztejn; Jesse Clark; Paula M Luz (JMIR Publications, 2023)
BackgroundGay, bisexual, and other men who have sex with men (MSM) with a higher perceived risk of HIV are more aware of and willing to use pre-exposure prophylaxis (PrEP). PrEP is an effective HIV prevention strategy, but there is a lack of data on how PrEP use might moderate the relationship between sexual risk behavior and perceived risk of HIV. Moreover, most studies measure perceived risk of HIV via a single question. ObjectiveWe estimated the moderating effect of PrEP use on the association between sexual risk behavior and perceived risk of HIV, measured with the 8-item Perceived Risk of HIV Scale (PRHS), among Brazilian MSM. MethodsA cross-sectional, web-based survey was completed by Brazilian Hornet app users aged ≥18 years between February and March 2020. We included data from cisgender men who reported sex with men in the previous 6 months. We evaluated the moderating effect of current PrEP use on the association between sexual risk behavior, measured via the HIV Incidence Risk Index for MSM (HIRI-MSM), and perceived risk of HIV, measured by the PRHS. Higher HIRI-MSM (range 0-45) and PRHS (range 10-40) scores indicate greater sexual behavioral risk and perceived risk of HIV, respectively. Both were standardized to z scores for use in multivariable linear regression models. ResultsAmong 4344 cisgender MSM, 448 (10.3%) were currently taking PrEP. Current PrEP users had a higher mean HIRI-MSM score (mean 21.0, SD 9.4 vs mean 13.2, SD 8.1; P<.001) and a lower mean PRHS score (mean 24.6, SD 5.1 vs mean 25.9, SD 4.9; P<.001) compared to those not currently taking PrEP. In the multivariable model, greater HIRI-MSM scores significantly predicted increased PRHS scores (β=.26, 95% CI 0.22-0.29; P<.001). PrEP use moderated the association between HIRI-MSM and PRHS score (interaction term β=-.30, 95% CI -0.39 to -0.21; P<.001), such that higher HIRI-MSM score did not predict higher PRHS score among current PrEP users. ConclusionsOur results suggest current PrEP users have confidence in PrEP's effectiveness as an HIV prevention strategy. PrEP's effectiveness, positive psychological impact, and the frequent HIV testing and interaction with health services required of PrEP users may jointly influence the relationship between sexual risk behavior and perceived risk of HIV among PrEP users.